Necesidad de incorporar en el código de procedimiento penal y código orgánico de la función judicial la unidad de criminalística como órgano auxiliar de la función judicial - Pinto, Jorge Leonardo (2015)
My thesis took place because the old Code of Criminal Procedure and the new Code of Criminal Integral requires the Prosecutor to exercise the pretrial investigation and criminal proceedings, a situation that forces you to have apply to the exercise of its function tools, however , does not have them, the Judicial Police is the support unit that counts, does not have the necessary expertise and required to do research, because the human element exists but the technology does not exist in any province except even in the corners, on the other hand, crimes are committed in all parishes, cantons and provinces of Ecuador, and are becoming more innovative in criminology and technological field. The rapid advance of science and technology has made that criminals use various tools to hide their illegal therefore it is essential to count with a specialized criminology as a subsidiary body of the judiciary, a unit that is having its own budget and optimum technology for the investigation of crimes. For these reasons, it is necessary to be incorporated in the Code of Criminal Integral and the Organic Code of the Judiciary Forensic Unit as a subsidiary body of the judiciary, to enable and enhance the investigation of offenses committed.